The Influence of Corporate Social Responsibilty on Tax Avoidance - Endrawati, Endrawati; Dyana, Putri; Djefris, Dedy (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2024)
This research evaluates the disclosure of tax avoidance and corporate social responsibility in companies listed on the stock exchange and based on the age of the company. By using the effective tax rate indicator for tax avoidance and the Global Reporting Initiative for corporate social responsibility. This research was conducted on manufacturing companies in the basic materials sector listed on the IDX from 2018 to 2023. The sample selection in this study used the purposive sampling method and obtained 21 sample companies. The results of this study indicate that companies listed on the special and main monitoring boards tend to have higher corporate social responsibility disclosures and are more focused on social responsibility initiatives. This suggests that companies listed on the main and special monitoring boards are more focused on social responsibility, including environmental sustainability, human rights, and contributions to society. This research underscores the importance of the role of corporate social responsibility in creating long-term value and the competitiveness of the company. This research also shows that companies aged 5-10 years tend to reach the peak of disclosure in various aspects of corporate social responsibility. These results emphasize the importance of corporate social responsibility in creating a good reputation and supporting sustainable growth, especially in the context of companies of different ages.